STRUKTUR PERTUNJUKAN DAN FUNGSI KESENIAN KACAPI PANTUN DI DESA SIRNARESMI KECAMATAN CISOLOK KABUPATEN SUKABUMI PROVINSI JAWA BARAT - Ariwana, Tantan Tandira (LP2M ISBI Bandung, 2023)
Kacapi Pantun in Sirnaresmi village is a traditional Sundanese art in Kasepuhan Adat Banten. Kacapi Pantun is traditional art that has been passed down from generation to generation. Kacapi Pantun is a performance of the Kacapi art accompanied by songs or chants. The existence of Kacapi Pantun has begun to be forgotten, only a few people know about the Kacapi Pantun because of the changing times. This is a big problem for all of us as people who care about tradtional art.